2012
DOI: 10.1016/j.ydbio.2012.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Roles of N-glycosylation and lipidation in Wg secretion and signaling

Abstract: Wnt members act as morphogens essential for embryonic patterning and adult homeostasis. Currently, it is still unclear how Wnt secretion and its gradient formation are regulated. In this study, we examined the roles of N-glycosylation and lipidation/acylation in regulating the activities of Wingless (Wg), the main Drosophila Wnt member. We show that Wg mutant devoid of all the N-glycosylations exhibits no major defects in either secretion or signaling, indicating that N-glycosylation is dispensable for Wg acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
60
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 49 publications
5
60
0
Order By: Relevance
“…Many of these foci co-stained with an antibody against Wntless, which is known to be co-trafficked with Wg in vesicles ( Fig. 3A) (Tang et al, 2012). This indicates that Wg protein is indeed present in escort cells.…”
Section: Escort Cells Are the Predominant Source Of Wg For The Fsc LImentioning
confidence: 82%
“…Many of these foci co-stained with an antibody against Wntless, which is known to be co-trafficked with Wg in vesicles ( Fig. 3A) (Tang et al, 2012). This indicates that Wg protein is indeed present in escort cells.…”
Section: Escort Cells Are the Predominant Source Of Wg For The Fsc LImentioning
confidence: 82%
“…In testing three well-characterized signaling pathways, we found that WG accumulates, whereas both GBB and JEB are reduced in the Mgat1 null synaptomatrix. WG has two N-glycosylation sites, but these do not regulate ligand expression (Tang et al, 2012), suggesting WG build-up occurs owing to lost synaptomatrix Nglycosylation. Importantly, WG overexpression increases NMJ bouton formation similarly to the phenotype of Mgat1 nulls (Ataman et al, 2008;Korkut et al, 2009), suggesting a possible causal mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…All Wnts bar one (Drosophila WntD, see below) undergo post-translational glycosylation and acylation. The role of glycosylation is unclear, with some reports suggesting that it is largely dispensable (Mason et al, 1992, Tang et al, 2012, whilst others propose that glycosylation is important for efficient secretion (Komekado et al, 2007, Kurayoshi et al, 2007 but not for signalling activity (Kurayoshi et al, 2007). In contrast, acylation is essential for the secretion of Wnts as well as their signalling activity (Willert et al, 2003).…”
Section: Post-translational Modifications In the Er And Golgi Apparatusmentioning
confidence: 99%
“…No other secreted protein is known to undergo such modification (Hedgehog family members carry distinct lipids, namely palmitate and cholesterol). Several studies have investigated the role of Wnts' palmitoleate (Komekado et al, 2007, Tang et al, 2012. It is now widely accepted that lipidation occurs at a single serine residue and is essential for Wnt function (Janda et al, 2012, Takada et al, 2006.…”
mentioning
confidence: 99%